Advancements in biomaterials and scaffold design for tendon repair and regeneration - Ahmad Alhaskawi; Yanzhao Dong; Xiaodi Zou; Weijie Zhou; Sohaib Hasan Abdullah Ezzi; Vishnu Goutham Kota; Mohamed Hasan Abdulla Hasan Abdulla; Sahar Abdalbary; Hui Lu (Journal of Applied Biomaterials & Functional Materials)
Tendon injuries present a significant clinical challenge due to their limited natural healing capacity and the mechanical demands placed on these tissues. This review provides a comprehensive evaluation of the current strategies and advancements in tendon repair and regeneration, focusing on biomaterial innovations and scaffold design. Through a systematic literature search of databases such as PubMed, Scopus, and Web of Science, key studies were analyzed to assess the efficacy of biocompatible materials like hydrogels, synthetic polymers, and fiber-reinforced scaffolds in promoting tendon healing. Emphasis is placed on the role of collagen fiber architecture, including fiber diameter, alignment, and crimping, in restoring the mechanical strength and functional properties of tendons. Additionally, the review highlights emerging techniques such as electrospinning, melt electrowriting, and hybrid textile methods that allow for precise scaffold designs mimicking native tendon structures. Cutting-edge approaches in regenerative medicine, including stem cell therapies, bioelectronic devices, and bioactive molecules, are also explored for their potential to enhance tendon repair. The findings underscore the transformative impact of these technologies on improving tendon biomechanics and functional recovery. Future research directions are outlined, aiming to overcome the current limitations in scaffold mechanical properties and integration at tendon-bone and tendon-muscle junctions. This review contributes to the development of more effective strategies for tendon regeneration, advancing both clinical outcomes and the field of orthopedic tissue engineering.